Pengalaman Santriwati dalam Menghadapi Tekanan Ganda (Double Pressure) di Pondok Pesantren - Syafiqah Salsabila Subhan; Emilia Mustary; Astinah Astinah; Muhamad Haramain (Universitas Pahlawan Tuanku Tambusai, 2026)
The phenomenon of psychological pressure on female students in Islamic boarding schools (pesantren) is becoming an increasingly important issue to study, especially when this pressure arises simultaneously from the family and social environment of the pesantren. This condition is known as double pressure, a situation where an individual faces demands, expectations, and conflicts from two different sources simultaneously. Family pressure can take the form of academic demands, Quran memorization, and future hopes, while social pressure arises through friendship conflicts, ostracism, verbal bullying, and the need for social acceptance. This study aims to analyze the forms of double pressure experienced by female students, the psychological and social impacts they cause, as well as coping strategies and the application of tazkiyatun nafs in dealing with this pressure at the An-Nahdlah Islamic Boarding School in Makassar. The study used a qualitative approach with a phenomenological research type. Data were obtained through in-depth interviews, observation, and documentation of four female students experiencing double pressure. Data analysis was conducted using the interactive model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing. The results of this study indicate that the dual pressures faced by female students stem from the simultaneous demands of family and friendship dynamics at Islamic boarding schools. This situation results in psychological impacts such as stress, anxiety, emotional exhaustion, overthinking, decreased motivation to learn, and disrupted social relationships. To deal with these pressures, female students employ emotional, social, and religious coping strategies. The main findings of this study indicate that the practice of tazkiyatun nafs (selfcontrol) through prayer, supplication, dhikr (remembrance of God), reading the Quran, self-reflection (introspection), tawakal (religious devotion), and husnuzan (assertion) are the most dominant coping mechanisms in helping female students achieve inner peace and increase self-resilience. These findings contribute to the development of Islamic psychology studies and Islamic counseling in understanding the experience of dual pressures and strategies for managing them among female students in Islamic boarding schools.